ANALISIS DETERMINAN PENYALURAN KREDIT NEGARA-NEGARA DENGAN PENYALURAN KREDIT TERTINGGI DAN TERENDAH DI DUNIA - Puspita, Annisa Putri; Prestianawati, Silvi Asna (Contemporary Studies in Economic, Finance and Banking, 2024)
This research aims to analyze the determinants of domestic credit distribution in countries with highest and lowest lending in the world. This research uses a quantitative descriptive approach with data panel regression method. The data is secondary data from the World Bank from 2013-2019 in Georgia, Vietnam, Thailand, Norwegia, Korea, Cina, Madagaskar, Bulgaria, Guyana, Indonesia, Guatemala, and Bangladesh. The implication of this research is expected to be able to contribute towards government policy, namely improving credit quality in Georgia, Vietnam, Thailand, Norwegia, Korea, Cina, Madagaskar, Bulgaria, Guyana, Indonesia, Guatemala, and Bangladesh. The results show that GDP and tax are significant to domestic credit distribution in countries with highest and lowest lending in the world, while interest rates have no significant effect.